2013
DOI: 10.1186/1477-7819-11-163
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary benign metastasizing leiomyoma from uterine leiomyoma

Abstract: BackgroundBenign metastasizing leiomyoma (BML) occurs in a low proportion of uterine leiomyomas and treatment methods for BML are diverse and controversial. The study introduces preliminary experiences in the diagnosis and treatment of BML with the purpose of finding a suitable management strategy for these patients.MethodsThree patients with BML were treated in our department from April 2008 to July 2012. Each of these patients presented with multiple nodules in both lungs, where we performed video-assisted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 19 publications
0
48
0
Order By: Relevance
“…Hormonal treatment can be a therapeutic option for young women who desire to retain fertility and for whom oophorectomy is not an option [35]. However, the primary treatment has been advocated to be a radical surgical resection [3,36]. Depending on locations of the metastases and the hormone receptor status, treatment should be individualized for each patient.…”
Section: Discussionmentioning
confidence: 98%
“…Hormonal treatment can be a therapeutic option for young women who desire to retain fertility and for whom oophorectomy is not an option [35]. However, the primary treatment has been advocated to be a radical surgical resection [3,36]. Depending on locations of the metastases and the hormone receptor status, treatment should be individualized for each patient.…”
Section: Discussionmentioning
confidence: 98%
“…Although the biological behavior of BML suggested malignancy, the tumor is borderline, with benign histological features. A previous stuy demonstrated that the lungs are the most common site of metastases (6). Pulmonary BML may present as asymptomatic pulmonary nodules diagnosed incidentally, be synchronous with uterine leiomyomas or arise following hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Before making a diagnosis of BML, leiomyosarcoma or smooth muscle tumors of uncertain malignant potential must be excluded. In most cases, the morphological features and immunohistochemistry should be sufficient for identification, however, the final diagnosis of BML should only be made after a careful review of a substantial number of samples obtained from the primary legion to exclude even small foci of aggressive leiomyosarcoma …”
Section: Discussionmentioning
confidence: 99%